2009
DOI: 10.1097/mpg.0b013e318169330f
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary Medicine in Pediatric Patients With Inflammatory Bowel Disease: Results From a Multicenter Survey

Abstract: Objectives We examined the use of complementary and alternative medicine (CAM) at 3 US pediatric medical centers, comparing a group of children with inflammatory bowel disease (IBD) with children presenting with chronic constipation. Materials and Methods Surveys were administered by postal mail and at pediatric IBD centers in San Francisco, Houston, and Atlanta from 2001 to 2003. A comparison group consisting of pediatric patients with chronic constipation also was surveyed. Data were analyzed by t tests an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 19 publications
5
59
1
Order By: Relevance
“…Several large studies in the pediatric population have demonstrated that CAM is used for symptom management, and healthmaintenance or prevention, rather than treatment of specificconditions [3,4,6,21]. Moreover, many studies have found a higher CAM use among children with chronic conditions such as cerebral palsy [11,15], asthma [22], cancer [15,17,23,24], sicklecell anemia [25], IBD [10,15,16,18,20], and emergent illness [14,21]. The present study demonstrated that 27% of pediatric surgical patients had an experience of using CAM and the rate of CAM use in IBD patients was significantly higher compared with that in non-IBD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several large studies in the pediatric population have demonstrated that CAM is used for symptom management, and healthmaintenance or prevention, rather than treatment of specificconditions [3,4,6,21]. Moreover, many studies have found a higher CAM use among children with chronic conditions such as cerebral palsy [11,15], asthma [22], cancer [15,17,23,24], sicklecell anemia [25], IBD [10,15,16,18,20], and emergent illness [14,21]. The present study demonstrated that 27% of pediatric surgical patients had an experience of using CAM and the rate of CAM use in IBD patients was significantly higher compared with that in non-IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that CAM use in Japanese patients who had un-dergone operation for pediatric surgical disease had no relationship with sex, age, duration of disease, parents' use, and associated disorders. It has been previously reported that factors associated with pediatric use of CAM are a higher age [4,6], the patient's self-reported overall health [10], white ethnicity [10], higher education in the parent's career [4,6,10,14], use of prescribed medication [4], and use of CAM by a parent [4,6,15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that knowledge and use of complementary and alternative medicine correlates with level of education. 6,24 We report findings from the first study to examine key ethical and social issues regarding fecal bacteriotherapy as a treatment for IBD. Participants perceived FB as "natural" and similar to probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…3 As such, patients with ulcerative colitis frequently embrace alternative therapeutic options such as probiotics. [4][5][6] Fecal bacteriotherapy (FB) is an alternative microbiome-based therapy, also known as "human probiotic infusion", "stool transplant", "fecal transfer", or the more recently proposed term, "fecal microbiota transplantation" (FMT). Fecal bacteriotherapy involves collecting stool from healthy pre-screened donors, preparing it, and administering it to an individual with disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation